Celebrating a “Neo-cosmopolitan globaletic writer” - Quayum, Mohammad Abdul (International Islamic University Malaysia, 2014)
Provides an overview and theoretical analysis of the items published in Vol. 8, No. 1 of the Asiatic journal.